Ašarų konceptualizavimas lietuvių ir latvių frazeologijoje - Kvašytė, Regina; Župerka, Kazimieras (Baltistica, 2011)
CONCEPTUALISATION OF TEARS IN LITHUANIAN AND LATVIAN PHRASEOLOGY The analysis of the collected material shows that the conceptualisation of tears in the Lithuanian and Latvian languages varies considerably. Though the material for the present analysis was collected from Lithuanian and Latvian dictionaries and collections of proverbs which differed in their scope and thoroughness and were often based on different principles of compilation, it provides sufficient data for grasping the main trends in the conceptualisation of tears. Lithuanians and Latvians frequently conceptualise tears in the same or a very similar way (many cases coincide with conceptualisation of tears in other languages). However, the analysis of the collected material and the contrastive studies of the Lithuanian and Latvian languages carried out to date prompt a tentative conclusion that tears take up more room in the world view of the Lithuanian language, i.e. they are more significant as a sign of a person’s emotional state. A comparison of the conceptualisation of tears in folk songs of both Baltic nations as well as the analysis of the verbs verkti / raudāt, their synonyms and derivatives in the contemporary language corpora are necessary in order to draw more valid conclusions.